2013
DOI: 10.1097/spv.0000000000000035
|View full text |Cite
|
Sign up to set email alerts
|

Safety Assessment of Myogenic Stem Cell Transplantation and Resulting Tumor Formation

Abstract: Whereas distant migration was not encountered in the liver or lung, 2 transplanted rats developed abnormal foci of growth, that is, tumors, from the external anal sphincter-raising further safety questions. Additional evaluation of these foci seemed benign. Possible explanations include cell trapping, stem cell overgrowth, and/or paracrine factors. The lack of cell migration supports that future investigation of safety parameters could focus locally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…Jacobs et al found no evidence of myogenic stem cell migration to the liver or lung. However, they detected local ectopic foci of growth in two treated rat anal sphincters after 30 days; the small tumors were benign tumors with no nuclear abnormalities [54]. In our study, normal histology was confirmed both by 3D mCT scanning of the whole sphincter sample area, as well as by selected histological sections.…”
Section: Discussionsupporting
confidence: 68%
“…Jacobs et al found no evidence of myogenic stem cell migration to the liver or lung. However, they detected local ectopic foci of growth in two treated rat anal sphincters after 30 days; the small tumors were benign tumors with no nuclear abnormalities [54]. In our study, normal histology was confirmed both by 3D mCT scanning of the whole sphincter sample area, as well as by selected histological sections.…”
Section: Discussionsupporting
confidence: 68%
“…Finally, our present results show that SC therapy on this model is safe, as no serious adverse reactions or neoplastic processes were observed. In this field, there is a worrisome paper in which 2/24 rats receiving 5 × 10 6 myogenic SCs developed local abnormal foci of growth that were benign[ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also in 2013, Jacobs et al[ 47 ] published the first study with a safety concern. Here, 33 female virgin SpragueDawley rats received surgical anal sphincter transection and repair, after which 24 underwent the injection of 5.0 × 10 6 allogeneic MDSCs and nine served as the sham control.…”
Section: Animal Studies Publishedmentioning
confidence: 99%
“…All investigations, except two, confirm the safety and absence of relevant adverse events. There is one alert with local injection (two local benign foci of growth in nearly 400 published injected animals)[ 47 ] and another with systemic (mortality increment associated with pulmonary embolisms)[ 42 ], possibly due to the high doses employed.…”
Section: Animal Studies Publishedmentioning
confidence: 99%